Exchange Rate Assessments : Methodologies for Oil Exporting Countries - de Carvalho Filho, Irineu; Bems, Rudolfs (Washington, D.C. : International Monetary Fund, 2009)
Are the current account fluctuations in oil-exporting countries "excessive"? How should their real exchange rate respond to the evolution of external (and domestic) fundamentals? This paper proposes methodologies tailored to the specific features of oil-exporting countries that help address these questions. Price-based methodologies (based on the time series of real effective exchange rates) identify a strong link between the real exchange rate and the terms of trade, but have relatively limited explanatory power. On the other hand, an empirical model of the current account, which fits oil exporting countries' data well, and an intertemporal model that takes into account the stock of oil reserves provide useful benchmarks for oil exporters' external balances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet